Canadian Marxists and the search for a third way - Campbell, J. Peter, 1952- (McGill-Queen's University Press, 1999)
"In this study of the theory and practice of four Canadian socialists whose names are known but whose lives, thoughts, feelings, and political beliefs are not, Peter Campbell explores the ideas and actions of four individuals - Ernest Winch, Bill Pritchard, Arthur Mould, and Bob Russell - who made major contributions to the history of the Canadian left. Campbell traces their childhoods in late Victorian England and Scotland, explores their early political and religious influences, details their involvement in the labour and socialist movements of Canada, and assesses their legacy to the Canadian working class."--Jacket